EVALUATION OF LOCAL ECONOMIC ACTIVITIES AS ELEMENTS OF THE DEVELOPMENT OF SMALL AND MEDIUM-SIZED CITIES - Budzeń, Daniel; Sobczyk, Andrzej (Zeszyty Naukowe UPH seria Administracja i Zarządzanie, 2021)
The concept of local development factors has gained in importance in the context of the reduction of existing resources, especially financial ones. The purpose of the present study is to evaluate localized economic activity as an endogenous factor in the development of small and medium-sized cities. Therefore, the individual sources of income of residents were examined on the basis of the data submitted with their tax declarations. The study covered the years 2016-2018, and included 255 small and medium-sized Polish cities that are revealing a depletion of their socio-economic functions. In order to assess local economic activities, the normalization method was used to compare the cities in terms of their potential. The results thus obtained allow for conclusions to be drawn on the importance of various sources of revenue to the development of cities, and are complementary to the analyses carried out so far in this area.